2018
DOI: 10.1186/s12913-018-2889-0
|View full text |Cite
|
Sign up to set email alerts
|

Navigation delivery models and roles of navigators in primary care: a scoping literature review

Abstract: BackgroundSystems navigation provided by individuals or teams is emerging as a strategy to reduce barriers to care. Complex clients with health and social support needs in primary care experience fragmentation and gaps in service delivery. There is great diversity in the design of navigation and a lack of consensus on navigation roles and models in primary care.MethodsWe conducted a scoping literature review following established methods to explore the existing evidence on system navigation in primary care. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
179
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 180 publications
(190 citation statements)
references
References 51 publications
9
179
0
2
Order By: Relevance
“…To the best of our knowledge, no previous systematic synthesis of existing literature, using a realist lens, has explored how this role can be implemented optimally. Other reviews have looked more at clinical navigation, rather than the use of local assets to address social determinants of health [34,35], have not adopted a realist lens when working with data [36][37][38] or have not focused specially on connector schemes [39]. A realist review that explored social prescribing more broadly described link workers as essential but not enough, on their own, to ensure that desired outcomes are achieved [15]; other elements, as touched on in our review, need to be in place, such as a vibrant VCS, changing the medical model focus in some health settings, and a shift in the mindset of patients.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, no previous systematic synthesis of existing literature, using a realist lens, has explored how this role can be implemented optimally. Other reviews have looked more at clinical navigation, rather than the use of local assets to address social determinants of health [34,35], have not adopted a realist lens when working with data [36][37][38] or have not focused specially on connector schemes [39]. A realist review that explored social prescribing more broadly described link workers as essential but not enough, on their own, to ensure that desired outcomes are achieved [15]; other elements, as touched on in our review, need to be in place, such as a vibrant VCS, changing the medical model focus in some health settings, and a shift in the mindset of patients.…”
Section: Discussionmentioning
confidence: 99%
“…While there is no commonly accepted definition of system navigation, we considered system navigation to refer to an individual or a team engaging in specific activities that include the following concepts: (i) facilitating access to health-related programs and social services for patients/families and caregivers; (ii) promoting and facilitating continuity of care; (iii) identifying and removing barriers to care; and (iv) effective and efficient use of the health-care system for both patients/families, caregivers, and practitioners. 44 A recent scoping review involving 34 studies on system navigation reported that because of the diversity of navigation models in the literature, and the lack of suitable research designs, it is difficult to draw conclusions regarding the effectiveness of system navigation. 44 However, one study was found that demonstrated the effectiveness of a Stroke Navigator role in increasing access to comprehensive, strengths-based assessment, planning, and referral facilitation.…”
Section: Interventionmentioning
confidence: 99%
“…Volunteers could work as extensions of primary care teams by: establishing stable relationships with patients, helping motivate lifestyle change and helping patients navigate the healthcare system. Helping motivate behaviour change through counselling techniques and peer support is common among health promotion volunteer programs (Crane-Okada et al, 2012;Ginis et al, 2013;Webel et al, 2010;Wu et al, 2012), while system navigation has become an increasingly recognised set of activities in primary care (Carter et al, 2018;Valaitis et al, 2017) and other settings (Manderson, McMurray, Piraino, & Stolee, 2012;Pedersen & Hack, 2010). Some navigation activities are best carried out by professionals, yet some (e.g.…”
mentioning
confidence: 99%